PENGARUH EDUKASI VIDEO BANTUAN HIDUP DASAR (BHD) TERHADAP TINGKAT PENGETAHUAN SISWA-SISWI KELAS X DI MADRASAH ALIYAH YPI MEKARJAYA - A, Sulastri; B, Rustandi; FT, Purwanti (SINERGI : Jurnal Riset Ilmiah, 2025)
Background: Basic Life Support (BHD) is an important first step in managing sudden cardiac arrest before medical personnel arrive. However, the level of public knowledge, especially school students, about BHD is still low. Education through video media is expected to be an effective method in improving students' understanding of this lifesaving action. Objective: This study aims to determine the effect of video education on the level of knowledge of class X students at MA YPI Mekarjaya. Research Methods: This study used a pre-experimental design with a one-group pretest-posttest design. Where the level of knowledge of class X students was measured before and after being given education. The study sample consisted of 40 students selected using total sampling technique, 10 respondents for preliminary study and 30 respondents for research. Data were collected through questionnaires before and after the video education intervention, then analyzed using the Wilcoxon statistical test.  Results: The results showed a significant increase in students' knowledge level after being given video education (p<0.05). This proves that the use of video media in health education can improve students' understanding of BHD. Conclusion: Video education is an effective method in improving students' knowledge about Basic Life Support. Therefore, this approach can be used as a health education strategy